SEXUAL HEALTH AMONG YOUTH-AT- RISK IN KUALA LUMPUR - Ibrahim, NasrudinSubhi, Fauziah (International Journal of Psychosocial Rehabilitation, 2020)
Sexual health is an important element in shaping the well-being of adolescents in addition to physical, intellectual and spiritual health. Therefore, this article is intended to (1) measure the extent of sexual health and (2) identify the influence of factors affecting sexual health among adolescents living in public housing flat projects (PPR) around Kuala Lumpur. The study was conducted using a quantitative cross sectional design involving 244 adolescents. The data were analyzed by using descriptive and stepwise multiple regression test. Descriptive analysis shows that 77.5 percent of adolescents living in PPR show low levels of sexual health and need to be improved. Multiple regression analysis found that the social media useage factor (β = 0.0.215, p